Komunikasi Terapeutik Dalam Asuhan Keperawatan Di Ruangan Rawat Inap Kelas III RSUD Prof. Dr. W.Z. Johannes Kupang - Maria Yulita Nara (Jurnal Communio : Jurnal Jurusan Ilmu Komunikasi, 2020)
Research with the title "Therapeutic Communication in Nursing Care in Class III Inpatient at the Prof. DR. W.Z. Johannes Kupang Hospital "is based on the importance of the therapeutic communication of nurses and patients at Prof. DR. W.Z. Johannes Kupang Hospital. This study focuses on how therapeutic communication in nursing care in class III inpatient at the Prof. DR. W.Z. Johannes Kupang hospital with the aim to analyze therapeutic communication in nursing care in inpatient room class III of Prof. DR. W.Z. Johannes Kupang hospital. Case study method is used in this research. The results of this study indicate that in the nursing care process that takes place in inpatient rooms of class III at Prof. DR. W.Z. Johannes Kupang hospital, the four stages of therapeutic communication can be found in the three parts of the therapeutic communication process, namely when the patient enters, when giving nursing care, and when the patient is discharged. The pre-interaction stage and the introductory stage appear in the communication process when the patient enters. The work phase which is the core of the therapeutic communication process appears in the communication process at the time of nursing care. The last stage is the termination stage which is divided into temporary termination stages, which is seen in the communication process of nurses and patients each time the nurse finishes providing routine nursing care every day. The final termination stage that appears in the nurse's communication with the patient is when the patient is declared allowed to go home or when the patient dies. Participants involved in the therapeutic communication process are not only nurses and patients but is also supported by doctors and patients' families. In the end these stages are interrelated with one another and create a fairly good communication process in nursing care in class III inpatients at the Prof.. DR. W.Z. Johannes Kupang hospital.